JUMPING TRAINING OF VOLLEYBALL PLAYERS OF SPORTS SCHOOLS FOR CHILDREN AND YOUNG PEOPLE - Nomozov , Abdurashid Tollibayevich (Innovative Development in Educational Activities, 2024)
The article examines the development of jumping endurance of volleyball players of sports schools.